Utilizing Graphic Organizers to Enhance Retention of Knowledge in ESL Writing Skills - Nair, Subadrah Madhawa; Zainudin, Rozariah; Krishnasamy, Hariharan N; Siddique, Muhammad (UUM Press, 2025)
Purpose - Writing is a difficult skill to master and improve, especially for students who learn English as a second language. Thus, this study explores the impact of employing graphic organizers on the writing performance of Form Four students and their knowledge retention. These students were 16- year-olds at the time of study. Furthermore, the investigation delves into the perceptions of students on writing methods. Methodology - This study employed a quasi-experimental design. The experimental group received instructions applying graphic organizers and the control group received instructions applying the conventional method. Pre-test, Post-test 1 and Post-test 2 were utilized to collect the data. The sample comprised 120 Form Four students chosen as intact groups from two schools, there were 60 students in each group. The study lasted for 11 weeks. One-way ANOVA and Repeated Measures were used to analyze the data collected from the Pre-test, Post-test 1 and Post-test 2, while the qualitative data gathered from the semi-structured interviews were investigated using thematic analysis for emerging themes. Findings - The quantitative results indicate that the experimental group performed significantly better than students from the control group in their overall writing skills and retention of knowledge in writing Findings from the qualitative data supported the quantitative findings which revealed that incorporating graphic organizers in writing boosted students’ motivation in writing and facilitated their learning, especially in the domain of content, organization, elaboration of ideas, and language. Significance - ESL teachers could use graphic organizers as an alternative method to improve students’ writing skills. Teacher training should prepare teachers to use methods that effectively utilize graphic organizers in the writing process